A review of the etiology, biomechanics, diagnosis, and management of patellofemoral pain in cyclists - van Zyl, E.; Schwellnus, M. P.; Noakes, T. D. (International SportMed Journal, 2001)
Patellofemoral pain (PFP) is a common overuse injury in cycling, but its etiology in cycling is not well understood. It is associated with poor patellar alignment during knee movement from flexion to extension. Biomechanical factors associated with patellar malalignment include poor quadriceps function, vastus medialis obliquus insufficiency, extensive subtalar-joint pronation, and poor muscle flexibility. Factors in the biomechanics of PFP in cyclists include abnormal lower-limb biomechanics, incorrect bicycle and equipment setting, and incorrect training methods. Abnormal forefoot and rear-foot alignment are associated with patellar maltracking. There is anecdotal evidence that leg-length discrepancies and varus or valgus knee malalignment are implicated in PFP in cyclists. Incorrect equipment settings include saddle height, incorrect cleat position, and the type of cleat and shoe. Training factors associated with PFP in cyclists are hill training, cycling with high gears at a low cadence, and a sudden increase in training volume. The article reviews the etiology, biomechanics, clinical diagnosis, and management of PFP in cyclists.